Unilateral focal lesions in the rostrolateral medulla influence chemosensitivity and breathing measured during wakefulness, sleep, and exercise. Issue 5 (1st November 1999) - Morrell, M J; Heywood, P; Moosavi, S H; Guz, A; Stevens, J
Abstract : OBJECTIVES: The rostrolateral medulla (RLM) has been identified in animals as an important site of chemosensitivity; in humans such site(s) have not been defined. The aim of this study was to investigate the physiological implications of unilateral lesions in the lower brainstem on the control of breathing. METHODS: In 15 patients breathing was measured awake at rest, asleep, during exercise, and during CO2 stimulation. The lesions were located clinically and by MRI; in nine patients they involved the RLM (RLM group), in six they were in the pons, cerebellum, or medial medulla (Non-RLM group). All RLM group patients, and three non-RLM group patients had ipsilateral Horner's syndrome. RESULTS: Six of the RLM group had a ventilatory sensitivity to inhaled CO2 (V˙/PET CO2 ) below normal (group A:V˙/PET CO2, mean, 0.87; range 0.3–1.4 l.min -1 /mm Hg). It was normal in all of the non-RLM group (group B: V˙/PET CO2, mean, 3.0; range, 2.6–3.9 min -1 /mmHg). There was no significant difference in breathing between groups during relaxed wakefulness (V˙, group A: 7.44 (SD 2.5) l.min -1 ; group B: 6.02 (SD 1.3) l.min -1 ; PET CO2, group A: 41.0 (SD 4.2) mm g; group B: 38.3 (SD2.0) mm Hg) or during exercise (V˙/V˙O2 : group A: 21 (SD 6.0) l.min -1 /l.min -1 ; group B: 24 (SD 7.3) l.min -1 /l.min -1 ). During sleep, all group A had fragmented sleep compared with only one patient in group B (group A: arousals, range 13 to > 60 events/hour); moreover, in group A there was a high incidence of obstructive sleep apnoea associated with hypoxaemia. CONCLUSION: Patients with unilateral RLM lesions require monitoring during sleep to diagnose any sleep apnoea. The finding that unilateral RLM lesions reduce ventilatory sensitivity to inhaled CO2 is consistent with animal studies. The reduced chemosensitivity had a minimal effect on breathing awake at rest or during exercise.